Clinical conceptualization of workaholism: A comprehensive model. (November 2017) - Loscalzo, Yura; Giannini, Marco
Workaholism is a behavioral addiction that, while widely studied, is still lacking a definition shared by the scientific community. The aim of this theoretical paper is to propose a new model that is at the same time comprehensive and easy to test, with an approach based on a critical analysis of the literature. We give particular attention to reviews of literature and theoretical and empirical papers published since 2011, because even the most recent reviews do not fully encompass the last few years. We proposed a comprehensive model, which defines workaholism as a clinical condition that is characterized by both externalizing (i.e., addiction) and internalizing (i.e., obsessive-compulsive) symptoms and by low levels of work engagement; from this there arises the distinction between disengaged and engaged workaholics (i.e., a less impairing subtype of workaholism). Finally, we propose DSM-like criteria for workaholism and a research agenda for future studies.